Discovery of triazole derivatives for biofilm disruption, anti-inflammation and metal ion chelation - Hong, Shuang; Lu, Hongzhi; Tian, Dawei; Chang, Yue; Lu, Qi; Gao, Feng (Frontiers in Chemistry, 2025)
In the face of bacterial hazards to human health and resistance to multiple antibiotics, there is an urgent need to develop new antibiotics to meet the challenge. In this paper, the triazolyl heterocyclic (3-amino-1,2,4-triazole, D) was synthesised efficiently using thiourea as starting material. Finally, the end product E was obtained by aldehyde-amine condensation reaction and the structures of all compounds were determined by spectral analysis. In vitro antimicrobial activity showed that E10 had a MIC of 32 μg/mL against the tested Escherichia coli and 16 μg/mL against the tested Staphylococcus aureus strain. Meanwhile, E10 has a good anti-biofilm effect. Antibacterial mechanism studies have shown that E10 has a good membrane targeting ability, thus disrupting cell membranes, leading to leakage of intracellular proteins and DNA and accelerating bacterial death. In terms of anti-inflammation, E10 dose-dependently inhibits the levels of inflammatory factors NO and IL-6, which deserves further exploration in the treatment of asthma. The study of metal ion removal capacity showed that the synthesised triazole derivatives have high capacity to remove heavy metals Pb2+, Cd2+, Ca2+, Mg2+, Fe3+,Cr3+ and Al3+ in the range of 42%–60%.